2014
DOI: 10.1158/1535-7163.mct-14-0257
|View full text |Cite
|
Sign up to set email alerts
|

The CDK4/6 Inhibitor LY2835219 Overcomes Vemurafenib Resistance Resulting from MAPK Reactivation and Cyclin D1 Upregulation

Abstract: B-RAF selective inhibitors, including vemurafenib, were recently developed as effective therapies for melanoma patients with B-RAF V600E mutation. However, most patients treated with vemurafenib eventually develop resistance largely due to reactivation of MAPK signaling. Inhibitors of MAPK signaling, including MEK1/2 inhibitor trametinib, failed to show significant clinical benefit in patients with acquired resistance to vemurafenib. Here, we describe that cell lines with acquired resistance to vemurafenib sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 33 publications
8
119
0
Order By: Relevance
“…Based on other studies of CDK4/6 inhibitors in melanoma that revealed a predominant G 1 phase arrest with little or no apoptosis, we expected that P1446A-05 would cause some G 1 phase arrest. 5,24 Our results, however, are more in line with those achieved by dinaciclib, a specific inhibitor of CDK1/2/5/9, which also causes G 2 /M phase cell cycle arrest and apoptosis. 12,23 We validated that P1446A-05 inhibits the kinase function of CDK4 and CDK9, so while we are confident that the anti-proliferative effects produced by this drug resulted in some part from appropriate CDK inhibition, it is impossible to rule out contributory off-target effects.…”
Section: Discussionsupporting
confidence: 78%
“…Based on other studies of CDK4/6 inhibitors in melanoma that revealed a predominant G 1 phase arrest with little or no apoptosis, we expected that P1446A-05 would cause some G 1 phase arrest. 5,24 Our results, however, are more in line with those achieved by dinaciclib, a specific inhibitor of CDK1/2/5/9, which also causes G 2 /M phase cell cycle arrest and apoptosis. 12,23 We validated that P1446A-05 inhibits the kinase function of CDK4 and CDK9, so while we are confident that the anti-proliferative effects produced by this drug resulted in some part from appropriate CDK inhibition, it is impossible to rule out contributory off-target effects.…”
Section: Discussionsupporting
confidence: 78%
“…However, Cdk4/6 inhibitors have shown great efficacy when combined with other inhibitors targeting key mitogenic and/or survival pathways. Cdk4/6 inhibitors synergize strongly with inhibition of HER2, PI3K/mTOR, MEK, IGF1R/IR, and B-RAF (Finn et al 2009;Franco et al 2014;Heilmann et al 2014;Vora et al 2014;Yadav et al 2014). In 2015, the Food and Drug Administration granted accelerated approval to a combination of the Cdk4/6 inhibitor palbociclib and letrozole for the treatment of hormone receptor-positive advanced breast cancer (Finn et al 2015), and the efficacy of palbociclib in this setting has been confirmed in subsequent large-scale trials (Turner et al 2015).…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%
“…Preclinical evidence of effectiveness of the combination of CDK4/6 inhibitors with inhibitors of the MAPK pathway also exists, particularly in melanoma [Yadav et al 2014] and in colorectal cancer [Ziemke et al 2016]. Additionally, the PDK1 inhibitor GSK2334470 was synergistic with CDK4/6 inhibitors in breast cancer cell lines and in xenograft models and was able to restore sensitivity to CDK4/6 inhibitors [Jansen et al 2016].…”
Section: Cyclin-dependent Kinase 4/6 Inhibitors: Preclinical Activitymentioning
confidence: 99%